A FIGURATIVE LANGUAGE FOUND IN THE BEST SONG OF IMAGINE DRAGONS 2023 - Diah Elza Indayani; Fitri Palupi Kusumawati; Amirudin Latif (Journal of English Education and Entrepreneurship (JEEP), 2025)
The objectives of this research are to find out the types of figurative language utilized in the best song of imagine dragons 2023 and to find the contextual meaning of the figurative language utilized in the best song of imagine dragons 2023. The method utilized is qualitative descriptive in which the researcher acts as the main and supporting instrument like documentation and tabulation which are utilized to collect all data from all the songs that have been collected in the best song of Imagine Dragons 2023. The results of this research shows that there are 9 types of figurative languages such as metaphors, similes, oxymoron, hyperbole, metonymy, synecdoche, personifications, rhetorical questions, anaphora in the best song of imagine dragons 2023. In this case, metaphor is the most dominant figurative language. Therefore, it can be concluded that the best song of imagine dragons 2023 has a lot of figurative language to enhance, beautify, and provide a more meaningful message for readers. Besides that, researcher also recommendation for lectures or teachers in learning related to figurative language which should provide the basics before analyzing songs such as identifying themes and messages to be conveying. Then, for students that want to study figurative language in song to be able comprehend or identify various types of figurative language such as hyperbole, simile, metaphor, personification and oxymoron. Lastly, for researcher who is interested or want to research this topic, suggestion to utilize an interdisciplinary approach for combining literary analysis and musicological studies to gain a deeper comprehending of the impact of figurative language in music.